2022
DOI: 10.1101/gr.275672.121
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide transcript and protein analysis highlights the role of protein homeostasis in the aging mouse heart

Abstract: Investigation of the molecular mechanisms of aging in the human heart is challenging due to confounding factors, such as diet and medications, as well as limited access to tissues from healthy aging individuals. The laboratory mouse provides an ideal model to study aging in healthy individuals in a controlled environment. However, previous mouse studies have examined only a narrow range of the genetic variation that shapes individual differences during aging. Here, we analyze transcriptome and proteome data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 99 publications
3
21
0
Order By: Relevance
“…Despite heart tissue having far fewer significant sex effects than kidney or liver, consistent with our previous work 7 , they are still more consistent between proteins and transcripts than age effects.…”
Section: Age Effects Are Less Consistent Between Proteins and Transcr...supporting
confidence: 88%
See 2 more Smart Citations
“…Despite heart tissue having far fewer significant sex effects than kidney or liver, consistent with our previous work 7 , they are still more consistent between proteins and transcripts than age effects.…”
Section: Age Effects Are Less Consistent Between Proteins and Transcr...supporting
confidence: 88%
“…The co-regulation of the overall proteosome complex, encompassing the 20S catalytic core, its 19S regulator, and the 11S regulator, is multifaceted. We have previously shown that abundance of individual components and sub-complexes of the proteasome are influenced by genetic variation 14 and age 7 in genetically diverse mouse populations. In this B6 sample population where genetic variation has been fixed (excluding spontaneous mutations specific to individuals), the sub-complex structure of the proteasome, most notably the 20S catalytic core and 19S regulator, is reflected in the pairwise correlations between complex members.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All QTLViewer projects contain at least one dataset such as a table of physiological traits, gene expression, or protein abundance data. Using the JAX Center for Aging Research DO data from the heart as an example (https://churchilllab.jax.org/qtlviewer/JAC/DOHeart) (Gerdes Gyuricza et al 2022) we find transcript and protein data available. Users can switch datasets by clicking the selection box arrow next to the text “Current Data Set” (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…The Collaborative Cross (CC) and Diversity Outbred (DO) mouse populations are related MPPs that have been used to genetically dissect complex traits, including obesity (Svenson et al 2012), bone strength (Al-Barghouthi et al 2021), short-term memory (Hsiao et al 2020), and arsenic response (French et al 2015). As recombinant populations, the CC and DO are well-suited for mapping quantitative trait loci (QTL), which can be powerful in studies of -omic traits, including gene expression, protein abundance, and chromatin accessibility (Abu Toamih Atamni et al 2018; Aylor et al 2011; Chick et al 2016; Gerdes Gyuricza et al 2022; Keele et al 2020; Keele et al 2021; Keller et al 2018; Takemon et al 2021).…”
Section: Introductionmentioning
confidence: 99%